Energy Conservation: A Conceptual Framework of Energy Awareness Development Process - Choong, Weng Wai; Mohammed, Abdul Hakim; Alias, Buang (CRES, FKSG, 2006)
Energy is wasted each day due to lack of awareness among societies. Past research suggest that there are two main energy conservation methods – technology fixedandbehaviouralapproach.Technologyfixedisbasedoninstrumentssuch as motion sensor control lighting and photovoltaic. Behavioural approach requires changes in human attitudes by using motivation, raising awareness and skill developing. This paper intends to explore the roles of behavioural approach in promoting energy conservation through raising energy awareness. Two related theories– Information Processing Theory and Three Term Contigency were reviewed. The information processing theory explains how people perceive information from their environment, operates on it, integrate it with information available in the memory, and used the product as the basis for deciding how to perform. The three-term contingency theory was invented to experimentally analyze human and animal behaviour, by dividing the behaviour into three key parts which constitute - stimulus, operant response and reinforcer/ punishment. A conceptual framework of energy awareness development process was proposed based on these two theories. The conceptual framework consists of nine phases – energy awareness stimulus, transference methods, interpretation, comprehension, awareness, reinforcement, short term motivation, obedience and long term motivation. Energy awareness stimulus explains that employees can be stimulated to support an energy management program. Transference methods are techniques or tools that could effectively transfer the stimulus to the receiver. The stages of interpretation, comprehension and awareness is receiver dominant, meaning that these phases is beyond the control of the building or facility manager. Reinforcement phase is required to strengthens the association between a response and preceding stimuli. Short term motivation is whatever activities that make people to act voluntarily in a certain way and then to persist in the face of difficulty. Theemployeeis expected to be in the phase of obedience that shows the early success of the energy awareness development process. The long term motivation such as public recognition, personal pride and energy award should be introduced to the receivers so they can continuously practice energy conservation. Finally the paper explains that validations are required to determine the effectiveness of the conceptual framework and to identify desired improvement.